2022
DOI: 10.3389/fimmu.2022.820164
|View full text |Cite
|
Sign up to set email alerts
|

LPIN1 Is a Regulatory Factor Associated With Immune Response and Inflammation in Sepsis

Abstract: ObjectivesSepsis is a clinical disease that is typically treated in the intensive care unit, and the complex pathophysiology under this disease has not been thoroughly understood. While ferroptosis is involved in inflammation and infection, its effect in sepsis is still unknown. The study aimed to identify ferroptosis-related genes in sepsis, providing translational potential therapeutic targets.MethodsThe dataset GSE65682 was used to download the sample source from the Gene Expression Omnibus (GEO) database. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…The differentially expressed genes (DEGs) were filtered via the R software with P < 0:05 [12]. WGCNA is a systematic biological method for characterizing gene association patterns between different samples and can be used to identify highly synergistic sets of genes and to screen for candidate biomarker genes or therapeutic targets [13]. We used the WGCNA function package in R software to screen for gene modules associated with disease phenotypes and further analyzed the relationship between these modules and HB tumor samples.…”
Section: Microarray Datamentioning
confidence: 99%
“…The differentially expressed genes (DEGs) were filtered via the R software with P < 0:05 [12]. WGCNA is a systematic biological method for characterizing gene association patterns between different samples and can be used to identify highly synergistic sets of genes and to screen for candidate biomarker genes or therapeutic targets [13]. We used the WGCNA function package in R software to screen for gene modules associated with disease phenotypes and further analyzed the relationship between these modules and HB tumor samples.…”
Section: Microarray Datamentioning
confidence: 99%
“…We applied an integrated bioinformatics analysis to explore key regulators using NetworkAnalyst, a web-based visual analytics platform for comprehensive profiling, meta-analysis and systems-level interpretation of gene expression data (Zhou et al, 2019 ). The utility of NetworkAnalyst for identifying differentially expressed genes (DEGs) and pathways has recently been demonstrated (Santiago and Potashkin, 2015 ; Li et al, 2020 ; Dai et al, 2022 ). For example, network analyses have identified HNF4A and PTBP1 as effective biomarkers for Parkinson's disease (Santiago and Potashkin, 2015 ) and ELAVL1 and APP as crucial candidate genes for Crohn's disease (Li et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…46 Recent studies have identified LPIN1 as a regulatory factor linked to immune response and inflammation in sepsis. 47 both PCOS and ovarian cancer. 49 Consistently, earlier research emphasized the significance of NR4A1 in the differentiation and survival of Ly6C-monocytes, as well as their maturation from myeloid dendritic precursors.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, IR in PCOS has been linked to reduced Lipin 1β expression in visceral adipose tissue 46 . Recent studies have identified LPIN1 as a regulatory factor linked to immune response and inflammation in sepsis 47 . PCOS is shown to have a dysregulated immune response highlighted by the inflammation.…”
Section: Discussionmentioning
confidence: 99%